Quantitative polmerase chain reaction for the rapid prenatal diagnosis of homozygous α‐thalassaemia (Hb Barts hydrops fetalis) - Chan, Vivian; Yip, Ben; Lam, Y. H.; Tse, H. Y.; Wong, H. S.; Chan, T. K. (British journal of haematology, 2001)
A quantitative polymerase chain reaction (Q‐PCR) method based on the TaqMan technology has been devised for the prenatal diagnosis of homozygous α°−thalassaemia (south‐east Asian type deletion). Primers and TaqMan probes were designed to specifically amplify an α°‐thal chromosomal fragment or a normal α‐chromosomal fragment. Variations in input target DNA in individual sample wells were normalized by the simultaneous amplification of a β‐actin gene fragment and results expressed as a ratio to that of β‐actin. There was no overlap of the data between the homozygous α°‐thal, α°‐thal and normal subjects. Up to 5% maternal DNA (α°‐thal) contamination did not affect the specificity of the result. In 31 prenatal diagnoses, the result using Q‐PCR compared favourably with the gold standard of Southern hybridization of α‐genes.